Long-term results of cementless femoral reconstruction following intertrochanteric osteotomy - Merle, Christian; Streit, Marcus R.; Innmann, Moritz Maximilian; Gotterbarm, Tobias (International orthopaedics, 2012)
PurposeThe objective of this retrospective cohort study was to assess the long-term outcome of cementless femoral reconstruction in patients with previous intertrochanteric osteotomy (ITO).MethodsWe evaluated the clinical and radiographic results of a consecutive series of 45 patients (48 hips, mean age 50 years) who had undergone conversion hip replacement following ITO with a cementless, grit-blasted, double-tapered femoral component. Clinical outcome was determined using the Harris hip score. Stem survival for different end points was assessed using Kaplan-Meier survivorship analysis.ResultsAt a mean follow-up of 20 (range, 16-24) years, 11 patients (12 hips) had died, and no patient was lost to follow-up. Six patients (six hips) underwent femoral revision, two for infection, three for aseptic loosening and one for periprosthetic fracture. Mean Harris hip score at final follow-up was 78 points (range, 23-100 points). Stem survival for all revisions was 89% (95%CI, 75-95) at 20 years, and survival for aseptic loosening was 93% (95%CI, 80-98).ConclusionsThe long-term results with this type of cementless femoral component in patients with previous intertrochanteric osteotomy are encouraging and compare well to those achieved in patients with normal femoral anatomy.
Gesehen am 29.11.2018